A comment on Hamilton (2016) "Measuring sustainability in the UN System of Environmental-Economic Accounting". (June 2022) - Bazhanov, Andrei V.
Abstract: Hamilton (2016) shows that an imperfect economy with extraction cost and any substitutability among inputs is sustainable along an exponentially decreasing path of extraction (EDP) under a generalized Hartwick rule with resource rent measured in SEEA-2012 (System of Environmental-Economic Accounting) units. Mathematically, the result is correct. The problem is that Hamilton offers this approach as "the correct policy rule for sustainability", although this saving rule may be inapplicable to real economies because the prescribed investment may exceed output. In particular, the Cobb–Douglas economy's output goes to zero along EDP even if there is no cost, no health damage from resource use, and all output is invested. The prescribed investment is feasible for the economy with the infinite resource–capital elasticity of substitution. This economy also may be sustainable, depending on initial conditions, along EDP with a reasonable constant saving rate. This result extends Hartwick (2003) disclaimer about substitutability among inputs to the generalized version of the rule. Moreover, the result shows that the assessment of sustainability and accounting prices for real economies depends, besides allocation mechanism, on specification of technology and initial conditions. Highlights: Hamilton (2016) offers a sustainability rule for imperfect resource economies. The rule is a combination of a saving rule and a path of extraction. Cobb–Douglas economy collapses along this path of extraction for any feasible saving. The Hamilton (2016) rule may be inapplicable to real economies.